Comparison of seismic responses of atrium-style and frame-box metro stations in soft soil in shaking table testing. (November 2022) - Zhang, Zhiming; Yuan, Yong; Li, Chong; Yu, Haitao; Chen, Hong; Bilotta, Emilio
Abstract: The building of atrium-style metro stations has emerged as an alternative metro station in recent years compared with conventional frame-box metro stations, but past research has never caught up and principally focused on frame-box metro stations. When atrium-style and frame-box metro stations are connected to each other in the same metro line, their different longitudinal and transverse cross sections may induce differentiated dynamic responses during earthquakes. To explore the possible difference in seismic behaviors between atrium-style and frame-box metro stations, a series of shaking-table tests was performed on two soil-underground station systems, which shared equal seismic loads with base shaking of 0.1–1.0 g. Experimental results indicate at higher frequencies of the input motion, the atrium-style and frame-box stations show different effects on the dynamic response of the ground surface. Larger dynamic strains are observed in the frame-box station on corresponding cross-sections with respect to the atrium-style station. An obvious difference between atrium-style and frame-box stations is a relative acceleration between the side wall and the corresponding soil on both magnitude and trend with increasing shaking intensities. The experimental results provide insight into how atrium-style and frame-box metro stations behave differently when subjected to earthquake shaking, which can provide guidance for metro station designers.